EDITORIAL NOTE - Hassan, Asmadi; Govindasamy, Geetha (WILAYAH: The International Journal of East Asian Studies, 2023)
The current volume includes various interesting articles which are informative, insightful as well as multidisciplinary, significant for academics, policy makers and students alike who are interested in East Asian affairs. This is in line with the aim of the journal in providing a platform for exchanges of ideas related to the East Asian region, with particular emphasis on Japan, China and Korea. This volume contains five articles focusing on three countries, contributed by scholars from various countries.